Afterword: Newsprint Worlds and Reading Publics in Colonial Contexts. Issue 2 (August 2020) - Newell, Stephanie
Abstract: This article discusses the ways in which newsprint allowed local contributors and readers in colonial settings to think across gender, race, and other core colonial subject-positions. It also asks about the extent to which the central role of men in controlling local print networks has implications for how we conceptualise "publics" and "public spheres" in the colonial era.